THE ROLE OF THE GOVERNMENT IN ADDRESSING POVERTY IN MALUKU: THE SYS-GMM APPROACH - Thenu, Tirsa Natasha; Adhitya, Dhian (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.07.TAHUN.2025, 2025)
This research aims to analyze the impact of social assistance funds, government spending in the education sector, and government spending in the health sector on the poverty rate in Maluku Province. This province has a relatively high poverty rate compared to the national average and faces structural challenges such as limited infrastructure and access to essential services. The data used is panel data from 11 regencies/cities in Maluku during the period 2017–2023. The System Generalized Method of Moments (SYS-GMM) is the analysis method to capture both short-term and long-term dynamic effects and address potential endogeneity. The estimation results show that in the short term, social assistance and education spending have a negative and significant impact on poverty, while health spending shows a significant positive impact. In the long term, social assistance and education expenditures continue to show a significant impact on reducing poverty. The convergence analysis indicates that the gap in poverty levels among districts and cities has diminished by 26.41% (convergence) annually, particularly in regions with elevated poverty rates, assuming other factors remain constant (ceteris paribus). These findings underscore the importance of optimizing social assistance and investing in the education sector to alleviate poverty in Maluku. In addition, there is a need for evaluation and reform in managing health sector expenditures to reach people with low incomes more effectively.